EVIDENCE OF ORAL HISTORY ON HISTORICAL STUDIES IN THE BEGINNING OF REZEKNE HIGHER EDUCATION INSTITUTION - Čakša, Valda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article summarizes the information obtained in the 1990s periodicals on the necessity to found a higher education institution in Rezekne and in this context analyses the narratives of readers and graduates of historical studies kept in the Oral History Archive of Rezekne Academy Technology (RAT), paying the greatest attention to the description of the study process, as well as the reflection of the students and university lecturers. Theoretical framework of the research consists of the theoretical insights of Paul Thomson (2000) and Alessandro Portelli (1991) that the oral history provides an opportunity to extend and even change the content of the history aimed at making it democratic and more personal. The publication is executed as a thematically descriptive account of qualitative analysis of content of the press articles and interviews. In the course of its elaboration the author concluded that the analyzed narratives, indirectly confirming the historical developments of the Third Awakening, inform about the participants of the process of historical studies in the new higher education institution in Latgale region, while themes of the press publications allows tracing down the awareness of society about the foundation of the higher education institution and the beginning of its operation. The results of the research prove that the community spirit and the emotional uplift, typical of society during the final stage of awakening is present in the individual experience of the readers and graduates, who were the participants of the initial stage of historical studies in the Rezekne Higher Education Institution, both as a context and stimulus for a purposeful cooperation and interaction.